Post-fire salvage logging alters a key plant-animal interaction for forest regeneration - Castro, J.; Puerta-Pinero, C.; Leverkus, A. B.; Moreno-Rueda, G.; Sanchez-Miranda, A. (ECOSPHERE, 2012)
Post-fire salvage logging is widely implemented worldwide, but there is an increasing concern about its potential impact on the ecosystem. Moreover, there is scant information about the effect of salvage logging on ecosystem processes mediated by species interactions. We manipulated a burnt pine forest to experimentally analyze the effect of burnt-wood management on the colonization of Holm oak (Quercus ilex) mediated by acorn dispersal by Eurasian jays (Garrulus glandarius). Three replicates of three treatments were established in an 18-ha plot: salvage logging (SL), non-intervention (NI), and partial cut plus lopping (PCL; felling and lopping most of the trees but leaving all the biomass in situ). We hypothesized that different burnt-wood management could alter jays' landscape perception and thus the pattern of seed dispersal and seedling recruitment. We monitored jay abundance in each treatment for three winters and three breeding periods, and jay flights of potential acorn dispersal between nearby oak trees and the treatments. We also searched for oak seedlings recruited in the experimental plot for five years following the fire. Jays were recorded significantly more times (87%) in NI, and movements to this treatment during the acorn dispersal period were also more frequent (81% of the flights). Oak seedlings were also more abundant in NI (ca. 55%) than in SL or PCL (ca. 25% each), despite a strong effect of small remnants of live pines. The results show that the burnt forest, if unsalvaged, still provides a suitable habitat for jays, while salvage logging reduces the strength of this key plant-animal interaction for oak natural regeneration. Nonintervention policies after a forest fire therefore provide the opportunity for adaptive management that helps reduce restoration costs and increase the resilience of the system.
The following values have no corresponding Zotero field: pub-location: 1990 M STREET NW, STE 700, WASHINGTON, DC 20036 USA publisher: ECOLOGICAL SOC AMER
Keywords: Garrulus glandarius; jay-oak interaction; oak colonization; Quercus ilex; resilience; salvage harvesting; seed dispersal; Sierra Nevada National Park; succession